HARMONISASI HUKUM WARIS ISLAM DAN HUKUM ADAT: ANALISIS TRADISI PEMBAGIAN DAMAI DALAM KERANGKA MAQASHID SYARIAH - Muhammad Yassir; Hafazhah Ar Ra'd (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study aims to analyze the harmonization between Islamic inheritance law and customary law in the practice of (peaceful distribution) among the Muslim community in Pontianak City, as well as to assess its conformity with the fundamental principles of maqashid syariah. Using a qualitative descriptive approach, data were obtained through in depth interviews with relevant participants. The findings reveal that (peaceful distribution) represents a form of social adaptation driven by the desire to maintain family harmony, where customary norms and Islamic law interact flexibly. Although the practice does not always follow the formal provisions of faraidh, it emphasizes justice and public welfare through family consensus. Within the framework of maqashid syariah, this practice is relatively strong in preserving hifz al-nafs and hifz al-nasl, but remains weak in hifz al-din, hifz al-aql, and hifz al-mal. Due to limited understanding of inheritance law and the weak role of religious institutions. Overall, the study concludes that the flexibility of Islamic law enables adaptations to local cultural contexts, yet requires normative strengthening to ensure that the essential values of the syariah remain intact within customary practices.